Communicating accountability through social outcome reporting by non-govermental Islamic organisations in Malaysia / Salsabila Abd. Rahim - Abd. Rahim, Salsabila (2022)
The not-for-profit sector has an integral role in economic and community building within both the local and international contexts. Nevertheless, Not-for-Profit Organisations (NPOs) are often faced with deficient funding that limits organisational performance. One of the most difficult challenges faced by NPOs is efficient handling of funds, which is part of their main task. The high accountability pressure prompts NPOs to adhere to the stringent regulations set by primary funders, thus minimising information asymmetry while enhancing accountability through specific reporting. Having that said, this study looked into Social Outcome Reporting (SOR) and its relevance to Non-Governmental Islamic Organisations (NGO-is) on reporting accountability. The NGO-i refers to Not-for-Profit Islamic Organisations (NPIOs) registered under the NGO-i Guidelines outlined by the Majlis Agama Islam Selangor (MAIS) to execute activities associated with the social development and growth of Muslims across Selangor. The SOR offers outcome-based information on activities and programmes to NGO-i funders, demonstrates the significance of NGO-i to their beneficiaries, and endorses activities to ascertain consistent funding. Upon adopting the case study approach; semi-structured interviews, meeting observations, and document analysis were carried out in this qualitative study. Through the lens of Accountability and Organisational Learning concepts, Signalling Theory (Spence, 1973), and Coercive Isomorphism (DeMaggio & Powell, 1983); the study outcomes revealed that the coercive power of funders did influence NGO-is in the SOR practice. Nonetheless, the limited Organisational Learning structure noted in NGO-is seemed to hinder the coercive force in inspiring most of the organisations to implement the SOR. Essentially, this study proposes the need for MAIS as the funder to assist NGO-is in developing their Organisational Learning capability. MAIS may facilitate the deployment of SOR into NGO-is, mainly because the SOR practice serves as an important communication and monitoring tool for them to review the performance and accountability measures of NGO-is and eventually improve their funding-allocation decisions.